Preparation and characterization of a copper based Indian traditional drug: tamra bhasma - Wadekar, M. P.; Rode, C. V.; Bendale, Y. N.; Patil, K. R.; Prabhune, Asmita (Journal of Pharmaceutical and Biomedical Analysis, 2005)
The copper based Indian traditional drug `tamra bhasma' is administered for various ailments since long. Its synthesis involves treating metallic copper with plant juices and then repeated calcination in presence of air so that the metallic state is transformed into the corresponding oxide form traditionally known as `bhasma'. In this work, we present a systematic characterization of this traditional drug using various techniques like X-ray diffraction (XRD), scanning electron microscopy (SEM)-energy dispersive X-ray analysis (EDX), X-ray photoelectron spectroscopy (XPS), infrared spectroscopy (IR), thermogravimetry (TG) and surface area measurement. The results obtained were found to match very well with those of a standard copper oxide confirming the composition of the drug sample. In addition, some specific findings were also made which could help in interpreting the therapeutic properties of the traditional drug `tamra bhasma'. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: copper oxide; crystallite size; tamra bhasma; traditional medicine; XPS of copper oxide; XRD